Epidermoid Cyst in the Floor of the Mouth of a 3-Year-Old - Rossana Pascual Dabán; Eloy García Díez; Beatriz González Navarro; José López-López (Hindawi Limited, 2015)
Epidermoid cysts are a rare entity in the oral cavity and are even less frequent in the floor of the mouth, representing less than 0.01% of all the cases. We present the case of a 3-year-old girl with a growth in the floor of the mouth with 2 months of evolution and without changes since it was discovered by her parents. The lesion was asymptomatic; it did not cause dysphagia, dyspnea, or any other alteration. A CT scan with contrast was done which revealed the location and exact size of the lesion, allowing an intraoral approach for its excision. The histological examination confirmed the clinical speculation of an epidermoid cyst.